2013
DOI: 10.1002/jcb.24501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mesenchymal stem cells on inhibiting airway remodeling and airway inflammation in chronic asthma

Abstract: Previous studies proved that bone marrow-derived mesenchymal stem cells (BMSCs) could improve a variety of immune-mediated disease by its immunomodulatory properties. In this study, we investigated the effect on airway remodeling and airway inflammation by administrating BMSCs in chronic asthmatic mice. Forty-eight female BALB/c mice were randomly distributed into PBS group, BMSCs treatment group, BMSCs control group, and asthmatic group. The levels of cytokine and immunoglobulin in serum and bronchoalveolar l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 31 publications
0
33
3
Order By: Relevance
“…No significant effect was seen in 2 studies, including the Lathrop et al study [9,13]. MSC treatment led to a significant decrease in BAL IL-13 levels in 3 studies [9,15,17] (P < 0.001 to P < 0.05), including with treatment after allergen challenge [15], whereas BAL IL-13 levels were already low in controls in 1 study [25] and there was no significant change in 5 studies [12,13,20,23,24]. One short-term study that reported on IL-9 levels in BAL found a reduction with MSC treatment (P < 0.05) [26].…”
Section: Other Biochemical Outcomesmentioning
confidence: 61%
See 2 more Smart Citations
“…No significant effect was seen in 2 studies, including the Lathrop et al study [9,13]. MSC treatment led to a significant decrease in BAL IL-13 levels in 3 studies [9,15,17] (P < 0.001 to P < 0.05), including with treatment after allergen challenge [15], whereas BAL IL-13 levels were already low in controls in 1 study [25] and there was no significant change in 5 studies [12,13,20,23,24]. One short-term study that reported on IL-9 levels in BAL found a reduction with MSC treatment (P < 0.05) [26].…”
Section: Other Biochemical Outcomesmentioning
confidence: 61%
“…MSC administration occurred before allergen challenge most commonly but also occurred before sensitization [11,17,20,21] or after allergen challenge [12,14,15,18,22] in other studies. MSCs were administered intravenously in all but 3 studies [11,23,24] in which they were administered intratracheally.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have demonstrated the anti-inflammatory potential of MSCs in several murine asthma models induced by high-molecular-weight allergens (ovalbumin, ragweed, and aspergillus hyphal extract) [11,13,[22][23][24][25][26][27][28] and in a low-molecular-weight, toluene diisocyanate (TDI)-induced asthma model [14]. However, in most of these models, the MSCs were administered preventively, that is, during the immunization phase or concomitantly with the induction of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Increased IgG levels were also reported by Sauni et al, 2012. In a chronic asthmatic mouse model, it was found that administering MSCs could decrease airway inflammation and airway remodeling by elevating IL-12 concentrations and the number of regulatory T cells, resulting in the re-balance of the local immune system (Ge et al, 2013).…”
Section: Discussionmentioning
confidence: 62%